2020
DOI: 10.1111/jnu.12546
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Needs of Abused Chinese Women Through a Community‐Based Participatory Approach

Abstract: Purpose: Intimate partner violence against women is a priority global health issue. It has had serious negative consequences on women's health and has led to huge burdens on the community. Numerous interventions have been demonstrated to have positive effects, and the majority of them have been developed using a top-down approach. However, the specific needs of abused Chinese women have not been fully addressed; incorporating women's input seems to be an essential element for the success of any intervention. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Communities also benefit when findings are shared, instead of languishing in academic journals. Successful CBR projects have increased condom use and HIV testing among gay and bisexual men (Rhodes et al 2017); demonstrated that Somali communities in the United States are more amenable to violence interventions targeted at gangs than at radicalization (Ellis et al 2020); and led to the development of culturally appropriate programs for Chinese women who are victims of domestic abuse (Chow and Tiwari 2020).…”
Section: Successful Community-based Researchmentioning
confidence: 99%
“…Communities also benefit when findings are shared, instead of languishing in academic journals. Successful CBR projects have increased condom use and HIV testing among gay and bisexual men (Rhodes et al 2017); demonstrated that Somali communities in the United States are more amenable to violence interventions targeted at gangs than at radicalization (Ellis et al 2020); and led to the development of culturally appropriate programs for Chinese women who are victims of domestic abuse (Chow and Tiwari 2020).…”
Section: Successful Community-based Researchmentioning
confidence: 99%